A Vessel for the Complex Supplying and Wastes Collection of Inland Ships on the Danube - Peter Patek; Jaroslav Borsky; Ivan Kotvan (Communications - Scientific letters of the University of Zilina, 2019)
Safe and reliable outgoing/filling of fuels and collection of sewage is important for continuous navigation and environmental protection. The supply vessel on the base of DEIIb barge was designed and built up for these purposes. The investor is the Division Port of Slovak Navigation and Ports Comp. and the builder is H.A.W.K. Comp. in Bratislava. The design and construction are made by the Department of Cars, Ships and Engines, Slovak University of Technology in Bratislava. This contribution demonstrates the project and general arrangement of this vessel.